2014
DOI: 10.1136/bmjopen-2013-004001
|View full text |Cite
|
Sign up to set email alerts
|

Association of early adult modifiable cardiovascular risk factors with left atrial size over a 20-year follow-up period: the CARDIA study

Abstract: ObjectivesWe investigate how early adult and 20-year changes in modifiable cardiovascular risk factors (MRF) predict left atrial dimension (LAD) at age 43–55 years.MethodsThe Coronary Artery Risk Development in Young Adults (CARDIA) study enrolled black and white adults (1985–1986). We included 2903 participants with echocardiography and MRF assessment in follow-up years 5 and 25. At years 5 and 25, LAD was assessed by M-mode echocardiography, then indexed to body surface area (BSA) or height. Blood pressure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
(29 reference statements)
0
22
1
Order By: Relevance
“…Assessments of risk factor variables in the CARDIA Study have been previously described [22, 27]. Briefly, the use of anti-hypertensive medication and smoking status (current smoker, former smoker and never smoker) were self-reported, assessed using validated questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Assessments of risk factor variables in the CARDIA Study have been previously described [22, 27]. Briefly, the use of anti-hypertensive medication and smoking status (current smoker, former smoker and never smoker) were self-reported, assessed using validated questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…The recently published CARDIA (Coronary Artery Risk Development in Young Adults) study investigated the influence of modifiable cardiovascular risk factors on LA size in 2903 young adults (age 23–35 years) over a 20‐year follow‐up period . After a 5‐year period, investigators showed that diabetes was not associated with unindexed LA diameter and LA diameter indexed for body surface area or height.…”
Section: Left Atrial Structure and Function In Diabetesmentioning
confidence: 99%
“…Furthermore, increases in BMI and BP are main determinants of cardiac remodeling over decades of adulthood (21,22). In fact, more severe obesity appears to be implicated with hospitalization for HF in patients with type 1 diabetes (23).…”
Section: Discussionmentioning
confidence: 99%